Dysplastic Gangliocytoma and Partial Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1989)
The clinical, radiologic and EEG features of three children with dysplastic gangliocytoma of the cerebral hemispheres and drug resistant partial seizures are described from the Comprehensive Epilepsy Center and Department of Neurology, Miami Children's Hospital, Miami, FL.